Competition and Bank Lending Channels: Evidence from Bank-Level Data in Thailand - Jearviriyaboonya, Jakkrich; Sethapramote, Yuthana (Journal of Applied Economics and Management Strategy, 2019)
ABSTRACT This paper investigates the effect of competition on the bank lending channels of monetary policy in Thailand. In addition, we also examine the impact of foreign bank entry on bank lending channels. The panel data regressions were estimated using bank-level data. The competition variable was measured using the Lerner index, while the number of new player (foreign branch) entries and the limitations on foreign bank entries measured foreign bank penetration. The results showed three main findings. The higher market power or less competition in Thai banking may reduce the effectiveness of the monetary policy mechanism via the bank lending channel. Banks having higher capitalization may enhance loan growth. In addition, evidence was found that foreign bank penetration, measured by the number of new player entries in foreign branches, weakens the bank lending channel. Keywords: Competition, Thai Banks, Bank Lending Channel